Virtue ethics reimagined: Aristotelian, Islamic, and Pancasila perspectives on character formation - Arief Rahman; Irma Yurni; Wachid Pratomo; Nurasih Shamadiyah; Eka Jayadiputra; Ella Dewi Latifah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
This study integrates Aristotelian, Islamic, and Pancasila ethics to formulate an operational framework for fostering "just and civilized" character within Indonesia’s plural society. Using a qualitative philosophical approach and systematic literature review, the research employs descriptive-interpretative, comparative, and integrative synthesis analyses. Findings reveal distinct moral orientations: Aristotelian ethics emphasizes immanent practical rationality, Islamic ethics is grounded in transcendent spiritual growth, and Pancasila functions as a public normative ethic. The novelty of this research lies in its departure from "eclectic aggregation"; instead, it proposes a multi-layered integrative model that harmonizes practical wisdom (phronesis), spiritual purification (tazkiyat al-nafs), and social cooperation (gotong royong) without compromising the epistemological integrity of each tradition. Practically, this framework provides a robust conceptual roadmap for character education and public policy in Indonesia, offering a middle ground that bridges religious-transcendental values with secular-rational virtues to enhance social cohesion in a diverse national context. By positioning individual virtue as the foundation and the common good as the ultimate orientation, this synthesis ensures that Pancasila ethics remains a relevant and applicable moral guide for modern Indonesian society.